Investigating Oman’s environment for startup opportunities - Muthuraman, Subrahmanian (Edelweiss Applied Science and Technology, 2024)
Entrepreneurship significantly contributes to national economies globally, including in the Sultanate of Oman, which is prioritizing its Oman Vision 2040. A startup ecosystem has developed to address market failures and rectify the oversight of entrepreneurship’s role within the economic framework. The exploratory study aims to investigate and understand why Oman is appealing to entrepreneurs, as well as to examine the support provided by the country’s startup ecosystem for emerging businesses. This paper also aims to investigate the opportunities and challenges within Oman’s startup ecosystem. It also seeks to assess how effectively Oman’s environment fosters entrepreneurship by enhancing market opportunities and alleviating the challenges and obstacles encountered by startups. The Omani government has introduced several initiatives to enhance the contribution of small and medium-sized enterprises (SMEs) to the economy. Oman has been motivated to develop innovative business concepts and new products through unique experiences and creativity. However, they lack the qualities of opportunism and proactivity needed to turn these ideas into successful entrepreneurial ventures. The challenges in Oman stem from a weak innovation and entrepreneurship ecosystem, which significantly limits the ability of incubators to provide meaningful value. The primary challenge facing startup ecosystems is limited access to key resources that can improve the performance of firms. The research indicates a necessity for a cohesive environmental framework that unites the different components of entrepreneurship in Oman. The role of the government in fostering a positive entrepreneurial environment is crucial in encouraging the establishment of new startups in Oman. The Omani government has established various committees and annual plans to promote entrepreneurship. The presence of government support greatly enhances the viability of entrepreneurial ventures in Oman by offering robust support and management assistance will help ensure the sustainability of startups in Oman and their positive impact on the national economy. The policy should prioritize the development of the innovation and entrepreneurial ecosystem, while also enhancing the cultural framework that supports these initiatives, enabling incubators to operate effectively. Policymakers in Oman would prioritize the establishment of a supportive ecosystem aimed at fostering entrepreneurship, encouraging Omani citizens to embrace entrepreneurial initiatives.